Pengaruh Model Pembelajaran Teams Games Tournament (TGT) terhadap Keterampilan Servis Panjang Bulutangkis pada Siswa Kelas VIII MTs Negeri 16 Jombang - Laksono, Danur Satyo; Zoki, Achmed (MAN Insan Cendekia Jambi, 2024)
A teaching strategy called Teams Games Tournament (TGT) splits students into groups of five to six people with a range of skill levels. According to observations, this teaching strategy had not been used before, but the researcher used it in this investigation. The purpose of the study was to ascertain if the Teams Games Tournament (TGT) teaching paradigm affected the long serve abilities of the eighth-grade badminton players at MTs Negeri 16 Jombang. This study used a one-group pretest-posttest design, which is a quantitative quasi-experimental method. Students in the eighth grade from class VIII A at MTs Negeri 16 Jombang made up the research sample. With an average pretest score of 19.90, classified as low, and an average posttest score of 21.16, classified as high, the findings demonstrated a considerable change. A significant difference in the students' abilities before and after the TGT teaching model was implemented was shown by the significance value (sig) = 0.052, > 0.05, which was obtained from the data analysis using SPSS version 25. As a result, the Teams Games Tournament (TGT) teaching methodology has a good impact on the long serve badminton abilities of the eighth-grade students at MTs Negeri 16 Jombang, rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha).